Еколого-економічний аспект історії Степової Скіфії - Гаврилюк, Н.О. (Археологія, 1997)
Стаття присвячена питанням економічного розвитку Степової Скіфії. Виділяються та характеризуються еколого-економічні райони, які існували тут у IV ст. до н. е. Розглядається феномен «Малої Скіфії» на Дніпрі. Статья посвящена истории экономики Степной Скифии. Осмысливается материал ранее исследованных и вновь открытых памятников оседлости степных скифов. В их интерпретации применяется научный аппарат экономической географии — объект исследования — Степная Скифия — представляется в виде комплексной эколого-экономической системы. Закономерным явлением в развитии эколого-экономической системы является распад ее в силу различных причин на эколого-экономические районы. В экономике Степной Скифии это происходит в IV в. до н. э. В статье подробно рассматривается структура Каменского эколого-экономического района и высказывается предположение о существовании эколого-экономических районов в других областях Скифии. Вскрывается механизм взаимодействия этих районов и их роль в попытке выхода из намечающегося экологического кризиса степного сообщества. Вскрываются причины эколого-экономического кризиса степи в III в. до н. э., имевшего характер «пороговой катастрофы» и пути выхода из кризиса. The paper is devoted to history of economy of Steppe Scythia. Findings obtained from the studies of the previously known and newly excavated relics testifying to the settled way of life of the steppe Scythians are analyzed. To interpret the findings the scientific system of the economic geography of the object to be studied is used: Steppe Scythia is presented as a complex ecological and economic system. The disintegration of this system into ecological and economic regions as a result of different events is a natural phenomenon in development of the ecological and economic system. That process took place in the economy of Steppe Scythia in the 4th cent. В. C. Particular attention is paid in the paper to the structure of the Kamensky ecologo-economic region. A supposition is advanced that such ecologo-economic regions existed in other provinces of Scythia. The mechanism of interaction between those regions as well as their attempt to avoid the forthcoming ecolohical crisis of the steppe community is described. Reasons which entailed the ecologo-economic crisis in the steppe in the 3d cent. В. C. which was a «threshold disaster» and ways to overcome it are discussed.